Project x: my family ( guided/group reading notes) - Tregenza, Jo (Oxford University Press Karachi, 2008)
"Project X" is a structured reading program aimed at developing children's literacy skills through engaging stories and characters. Each book features dynamic narratives that encourage critical thinking and comprehension. The series covers various themes, including friendship, adventure, and problem-solving. Activities and discussion prompts are integrated to enhance understanding and foster a love for reading. Overall, "Project X" serves as an effective tool for teachers and students to explore reading in a fun, interactive way.